Professional Development and Science Teacher Effectiveness in Africa: A Study of South Western Uganda - Mwesigye, Seriano; Sekiwu, Denis; Edoru, John Michael (East African Journal of Education Studies, 2024)
Teacher Professional Development (TPD) has long been a factor in revolutionizing the quality of science education in Africa. Although the Ugandan government introduced many TPD initiatives, there have been noticeable failure rates in science subjects at the Uganda Certificate of Education (UCE) examinations countrywide. This study aims to interrogate the level of science teacher engagement in professional development, challenges hindering teacher access to TPD programs, and the correlation between TPD and teacher effectiveness in terms of science grades. Using the Mixed method design, a sample size of 100 science teachers was recruited. The major findings revealed glaring gaps relating to inadequate teacher involvement in professional development, lack of planning for professional training of science teachers, limited funding and negative attitude towards professional development by science teachers and the school administration. The study provides a promising revelation that engagement in TPD positively correlates (π = 0.473, p < 0.01) with science teacher effectiveness. The study points to a critical argument that in order to deconstruct the narrative that STEM performance is supposed to be low and historically few students take on these disciplines, there is a need to invest in professional growth for science teachers